Peripartum care for mothers diagnosed with hepatitis B during pregnancy: A survey of provider practices - Kwong, Allison J. (Matern Child Health J, 2018)
OBJECTIVES: Hepatitis B (HBV) remains a significant public health burden, despite effective therapy. Routine HBV screening is recommended during pregnancy to reduce the risk of vertical transmission, but the rates of follow-up care peripartum are low. The aim of this study was to evaluate physician practices and knowledge regarding HBV in women diagnosed perinatally. METHODS: A survey was distributed to obstetricians and midwives within the Partners HealthCare system at Brigham and Women’s Hospital and Massachusetts General Hospital. RESULTS: Of 118 survey respondents (response rate 56%), 97% reported that they always tested for hepatitis B, and 77% referred new diagnoses of HBV during pregnancy to a HBV specialist for further care. Only 10% of respondents reported that there was formal referral mechanism in place to facilitate follow-up care for mothers diagnosed with hepatitis B infection. 91% of survey respondents selected hepatitis B surface antigen as the correct screening test, and 76% selected hepatitis B immune globulin (HBIG) with vaccination for the newborn as the correct prophylaxis regimen. Only 40% and 51% of respondents accurately identified serologies that were consistent with acute and chronic infection, respectively. CONCLUSION: Routine screening for HBV in this population presents an important opportunity to identify cases and to reduce the public health burden of this disease. Providers were somewhat knowledgeable about HBV, but the lack of formal referral mechanism may explain why HBV follow-up is suboptimal in this healthcare system. Supplemental provider education and formal linkage to care programs may increase rates of follow-up HBV care.